Influence of kinematics variables on distance running during competition - Hussain, I.; Ansari N. W. (International Journal of Sports Science, 2013)
Running is popular for the fitness and competitive sports. But it requires the correct body technique for get success in both areas. Athletes from different sports must understand the importance of their movement to enhance their performance. The 5000m race is a premier event in the sport of track event that demands technique. Good running technique will lead to improvements in 5000m race because basic action of 5000m race runner is of considerable importance for competitive athletes. Biomechanists are continuously engaged in sports, committed to improve athletes running mechanics, not only to perform at higher intensity but also for overall running mechanics. However, very little studies on kinematics analysis have been done on 5000m race. Thus this study has been designed to examine importance of 5000m race track runner`s kinematics. To develop foundational base of running mechanics for 5000m race runner training. A sample of twenty seven male All India Intervarsity players with age, weight and height ranged 18-25yrs, 49-75kg and 156-185cm were selected. The data were generated by capturing the videos during competition with two Synchronized Panasonic F15 S-VHS video camera. Coral-5&9, Link MPEG Player, SthSDVD, Photo Studio, SPSS and office Excel software were used to analyze the recorded data. ANOVA was used to analysis the data, and the result of the statistical analysis for kinematics variables: knee extension and flexion, hip extension and flexion, shoulder rotation and extension, ankle angel a landing and take- off and heel angle at take-off have shown significant influence on running style.